26. ANALYSIS OF SOME HEMATOLOGICAL AND IMMUNOLOGICAL PARAMETERS IN FULL TERM NEONATES WITH SEPSIS AT VIETNAM NATIONAL CHILDREN'S HOSPITAL, 2020 (Vietnam Journal of Community Medicine, 2023)
Objectives: The study was conducted to determine the biochemical and hematological parameters in full-term neonates with sepsis in order to evaluate the role of these parameters in sepsis diagnosis.Study methods: The study was designed using experimental descriptive method at the laboratory.Results: The mean Hct in the full-term neonates with sepsis was 40.3% ± 7.3%. The overall Hct deficiency was 72.9% (62/85). The overall increased white blood cell count was 41.2%. The mean white blood cell count per litre of peripheral blood was 16.78 ± 10.31 (109/L). The mean white blood cell count in the term neonates with sepsis caused by Gram positive bacteria, Gram negative bacteria, and fungi was 19.48 ± 11.22, 19.97 ± 13.45, 17.17 ± 10.05 respectively. The difference was not statistically significant in the mean value of white blood cell count in each etiology with 19.48 ± 11.22 of S. aureus, 19.48 ± 11.22 of K. pneumonia, 19.97 ± 13.45 of E.coli, 17.17 ± 10.05 of agalactiae, 11.75 ± 7.46 of Candida and 17.42 ± 10.80 of other causes, p > 0.05. The average number of platelets in the blood was 211.69 ± 204.45, and 49.6% of the neonates had thrombocytopenia (platelets < 100x109/L). The mean blood CRP was 84.2 ± 76.8 mg/L, and 88.3% (75/85) of the neonates had an increased CRP.Conclusions: The mean Hct in the full-term neonates with sepsis was 40.3% ± 7.3%. The overall Hct deficiency was 72.9%. The rate of increased white blood cell count was 41.2%. The mean white blood cell count per litre of blood was 16.78 ± 10.31. The mean platelet count in the blood was 211.69 ± 204.45, with 49.6% of thrombocytopenia. The increased CRP was 88.3%.
Keywords: Sepsis, neonates, full term.